1938
DOI: 10.1590/s0074-02761938000400008
|View full text |Cite
|
Sign up to set email alerts
|

Infecções experimentaes na Leishmaniose visceral americana

Abstract: Passando em revista as experiencias de infecção que effectuamos e que acabamos de relatar, vemos que, as culturas isoladas de casos de Leishmaniose visceral americana quer do homem quer do cão, são capazes de infectar hamsters, rhesus e cães de maneira identica ao que acontece com as outras formas de Kala-Azar. Notamos ainda que a evolução da doença e as lesões observadas nos animaes assim infectados, se assemelham ao que tem sido observado nessa enfermidade aproximando-a de maneira singular do Kala-Azar medit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…This species belongs to the L. donovani complex [2], [3]. Recently, a study that compared microsatellite profiles [4] strongly supported the hypothesis that L. infantum was introduced in the New World during or after the Colonial period, and this introduction may have occurred more than once, as previously proposed [5], [6], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 68%
“…This species belongs to the L. donovani complex [2], [3]. Recently, a study that compared microsatellite profiles [4] strongly supported the hypothesis that L. infantum was introduced in the New World during or after the Colonial period, and this introduction may have occurred more than once, as previously proposed [5], [6], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 68%
“…Because Aristides Marques da Cunha (1887–1949) and Evandro Serafim Lobo Chagas 10 (1905–1940) were, for unknown reasons, unable to infect laboratory animals with the parasite from Brazilian cases of VL while that was usually no problem with both L. donovani and L. infantum causing Old World VL, they thought that they had discovered a new species responsible for VL in the New World and named it Leishmania chagasi in 1937 [ 66 ]. However, 1 year later, Cunha reported that he succeeded in infecting animals with cultures isolated from cases of American VL and thus concluded that the agent of VL in Latin America is identical to L. infantum [ 67 ]. More recently, this notion has been supported by modern molecular analysis techniques showing that L. chagasi strains could not be distinguished from L. infantum strains [ 68 ].…”
Section: Origin Of the Genus Leishmaniamentioning
confidence: 99%
“…Vaccines 2023, 11, 1565 2 of 14 natural reservoirs because the parasites can survive in skin macrophages, facilitating the transmission to vectors [8]. Indeed, a substantial overlap between locations where human cases are detected and high canine seroprevalence have been reported, underscoring the close relationship between canine and human infections [8][9][10][11]. The vector Lutzomyia longipalpis, described by Lutz and Neiva (1912), accounts for 90% of VL transmissions in Latin America [12,13].…”
Section: Introductionmentioning
confidence: 99%